The pedagogy of hyperlinkages: Knowledge curatorialism and the archive of kindness - Auerbach, J. (South African Journal of Higher Education, 2022)
This article uses a student assessment developed in the “emergency” conditions of the Covid-19 pandemic in South Africa as a tool for refracting and reflecting (Strassler 2011) the changing realities of higher education around the world. It examines the Archive of Kindness as an example of the possibilities enabled by digitally mediated learning, as well as the challenges of teaching and learning in environments where students enter university with varying degrees of digital literacy and skill. It poses questions pertaining to the futures of higher education in a world in which biopolitics are increasingly determined by and through screens, and suggests that uncritical engagements with digital platforms and the corporate entities behind them pose dangers to emerging forms of citizenship. The article details the processes of knowledge curatorialism which are increasingly likely to determine the shape of learning in tertiary education, particularly within the university sector. Here, it argues that the Humanities and Social Sciences will need to play a leading role in providing the language and tools for thinking through the pedagogy of hyperlinkages, where the boundaries between online and offline spaces are increasingly difficult to parse.